Methods of Teaching the Technique of Athletics to Students of the Faculty of Physical Culture - Kozlova Galina Gennadievna (Zien Journals, 2022)
For the formation of independent, theoretical and practical training of students, the article provides a detailed description of the methodology for teaching the technique of athletics in the form of plan-schemes.
Keywords: Athletics; students; educational process; teaching methods